On the threshold of the Tunis School: The use of national references in the perception and promotion of the fine arts in Tunisia before the Second World War [English translation] - Messaoudi, Alain (Manazir Journal, 2021)
On the occasion of the inauguration of the first gallery founded by artists in Tunis, the painters Moses Levy, Pierre Boucherle, Antonio Corpora and Jules Lellouche published in 1936 a manifesto affirming their autonomy, beyond mercantile logics and national assignments. However, a national reading of their works prevailed in the press, at that time. This article proposes to put this founding event of the « École de Tunis » into context, by reinscribing it in a century-old history. This past is marked by the presence of French and Italian artists between 1840 and 1880, by the failure of a policy of asserting a French artistic model with an aborted project for a French museum around 1890, and by the affirmation of an artistic life characterised since the 1910s by its pluralism and even its eclecticism. This article thus intends to contribute, through the example of pictorial production, to the historicisation of discourses on the plurality or cultural identity of Tunisia, which are still today objects of debate. The translation of this article into English was made possible with the support of the University of Nantes and the Research Centre for Atlantic and International History (EA 1163 - Universities of Nantes and La Rochelle).